Historical legacies shape continental variation in contemporary mammal food webs - Chia Hsieh; Evan C. Fricke; Wei-Hao Lee; Daniel Gorczynski; Lydia Beaudrot (Proceedings of the National Academy of Sciences, 2026)
Contemporary ecological networks reflect the influence of evolutionary and ecological processes on species interactions. Additionally, late Quaternary megafaunal extinctions and subsequent range contractions have interrupted mammalian predator–prey interactions to differing degrees among continents. However, the extent to which species losses have shaped geographic variation in the vertical and horizontal structure of contemporary mammalian food webs remains poorly understood. Furthermore, the relative influences of species loss, evolutionary history, and contemporary environmental drivers on the structure of mammalian food webs have not been tested. Here, we assembled mammal food webs for 389 sites throughout the Neotropics, Afrotropics, and Indomalaya. We first examined variation among continents in food web properties, including predator–prey richness ratios, predator generality, prey vulnerability, and predator dietary specialization. We found that Neotropical food webs bear imprints of severe species loss, featuring smaller predators, lower predator generality, higher prey vulnerability, and reduced prey species availability compared to Afrotropical food webs, in which most large mammals persisted. Furthermore, we reveal that multiple historical legacies, including community lineage history, paleoclimatic variability, mountain uplift, and species losses, as well as contemporary environmental variability, collectively predicted variation in predator dietary niche breadth within continents. Our findings offer unique perspectives on how trophic interactions within food webs respond to species losses and how macroevolutionary and macroecological processes have shaped the biogeography of contemporary mammal food webs.